Our hidden conversations : what Americans really think about race and identity - Norris, Michele (Simon & Schuster, 2024)
"Our Hidden Conversations is a unique compilation of stories, richly reported essays, and photographs providing a window into America during a tumultuous era. This powerful book offers an honest, if sometimes uncomfortable, conversation about race and identity, permitting us to eavesdrop on deep-seated thoughts, private discussions, and long submerged memories."--